The COVID-19 pandemic and its impact on inequality of opportunity in psychological distress in the UK - Apostolos Davillas; Andrew M. Jones (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We use data from Wave 9 of UK Household Longitudinal Study (UKHLS) and the April 2020 Wave of the UKHLS COVID-19 survey to compare measures of ex ante inequality of opportunity (IOp) in psychological distress, as measured by the General Health Questionnaire (GHQ), before (Wave 9) and at the initial peak (April 2020) of the pandemic. Based on a Caseness measure, the prevalence of psychological distress increases from 18.3% to 28.3% between Wave 9 and April 2020. Also, there is a systematic increase in total inequality in the Likert GHQ-12 score. However, measures of IOp have not increased. Specifically, the proportion of total inequality attributed to circumstances has declined, consistent with the notion that the pandemic is, to some extent, a leveller as far as psychological distress is considered. A Shapley-Shorrocks decomposition analysis shows that in the pre-COVID-19 period the largest contributors to IOp were financial strain, employment status and housing conditions. In contrast, in April 2020, these factors decline in their shares and age and gender now account for a larger share. The contribution of working in an industry related to the COVID-19 response plays a small role at Wave 9, but more than triples its share in April 2020. Household composition and parental occupation also increase their shares during the pandemic.
Keywords: C1; D63; I12; I14; 330; COVID-19; inequality of opportunity; GHQ; mental health; psychological distress